DESIGN OF INTELLIGENT WAREHOUSING SYSTEM BASED ON DELTA CLOUND PLATFORM - Xie, Min; Guo, Shan; Qian, Danhao; Xiao, Maohua; Wu, Dan; Dai, Haoyue (International Journal of Mechatronics & Applied Mechanics, 2019)
With the development of science and technology, intelligent control technologies such as big data and cloud computing have also flourished, and logistics management and warehousing links have also ushered in challenges. The industrial cloud technology-based warehouse management system will be an inevitable choice for technological development and intelligent manufacturing. This paper expounds the development status, research direction and existing problems of intelligent warehousing, and puts forward the overall design of the intelligent warehousing system based on Delta Cloud platform. To implement the corresponding functions of the warehouse system, the hardware of PLC control system was carefully selected and programmable controller programming was designed.